DAKWAH MELALUI WEBSITE: STUDI KASUS www.dakwatuna.com - Anang Walian (Institut Agama Islam Negeri Bengkulu, 2016)
The preaching is an activity to communicate the message of Islam extensively to the communicant In its implementation, preaching can use the sophistication of communications media that relevant to modern era. The website is a service available in the internet network that can also be utilized to communicate the message of Islam to netizens. The preaching by website can be one option in contemporary media. This study takes cases from www.dakwatuna.com as one of interesting websites inIndonesia.